Perbedaan Gambaran Histopatologi Granuloma Paru Mencit Setelah Diinfeksi Mycobacterium tuberculosis dan atau Intervensi Silika (THE INFLUENCES OF TIME IN THE HISTOPATHOLOGY OF LUNG GRANULOMA IN MICE AFTER INFECTION OF MYCOBACTERIUM TUBERCULOSIS AND SILI - Linawati, Ni Made; Mayun, I Gusti Ngurah; Wiryawan, I Gusti Nyoman Sri; Budayanti, Nyoman Sri; Mertaniasih, Ni Made; Ratam, Fedik Abdul; Wande, I Nyoman; Ratnayanti, I Gusti Ayu Dewi; Wahyuniari, Ida Ayu Ika; Sugiritama, I Wayan; Arijana, I Gusti Kamasan (Jurnal Veteriner; Vol 14 No 1 (2013), 2013)
The characteristics of lung tuberculosis is granuloma, which is consisted of lymphocytes andmacrophages that show the interaction between immune cells and M.tb. Granuloma is the organizationprocess which is depend on lymphocytes invasion, adhesion molecules and chemokine fasilitation. Silicosiswhich is caused by silica, can influence granuloma in the lung. The features of granuloma is variationdepend on the elicited agent and immune reaction. The main purpose of this study was to prove thehistopathology differences of  mice lung granuloma caused by M.tb infection,  silica intervention and bothin 3th  and 7th weeks. It was 45 mice Balb-c strain, divided into 3 groups;  P1 got  M.tb infection with H37Rvstrain 105  perml,P2 got silica intervention with 60 micro litre and, P3 got both of M.tb infection and  silica intervention. Termination of each group were held on 3 and 7 weeks of intervention, continued byhistopathology examination. In the histopathology feature, we done semi-quantitative prosedure to measurelung damage by using Dormans scores; perivasculitis, peribronchiolitis, alveolitis and granuloma. Oneway anova to analysis the differences of histopathologycal result among these groups (P< 0,05).  Resultshowed the significant differences  among these group.  In the 3th weeks, we found  mild lung damage werehappened in all groups with granuloma, without necrosic (P1 and P2). In the 7th weeks we found  severe lungdamage in P3 with necrotic and fibrotic granuloma sign, with necrosis in P1, with fibrotic in P2.  Weconcluded the worst lung damage happened in 7th weeks in group which are got M.tb infection and silicaintervention, with granuloma characterictic of necrosic and fibrotic.
Keywords: Mycobacterium tuberculosis, silica, histopathology, lung granuloma